An axiomatic characterization of a generalized ecological footprint - Thomas Kuhn; Radomir Pestow; Anja Zenker (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2019)
The purpose of this paper is to propose an axiomatic characterization of ecological footprint indices. Using an axiomatic approach, we define a set of axioms to represent the properties considered appropriate to ecological footprint measures in general. It can be shown that there exists a generalized index which is unique up to a strictly increasing function of the world land area appropriated to satisfy human needs. As an implication, the well-known compound-based footprint index used by the Global Footprint Network can be characterized as a specification of the generalized index, only if proportionality in world land area use is additionally assumed and the norm is arbitrarily fixed, in terms of global hectares. Instead, we find that the applied methodology of normalization and standardization in the aggregation procedure of footprint indices is completely dispensible. In this respect, the proposition of generalized and axiomatically characterized indices for the measurement of the ecological footprint of human activity may be considered as the main contribution of the paper.
Keywords: Q13; Q41; Q43; C43; 330; Ecological Footprint Index; Axiomatic Foundation; Measurement Theory; Overshoot Day; Sustainable Welfare